2012
DOI: 10.1126/science.1226854
|View full text |Cite
|
Sign up to set email alerts
|

Optical Control of Protein Activity by Fluorescent Protein Domains

Abstract: Fluorescent proteins (FPs) are widely used as optical sensors while other light-absorbing domains have been used for optical control of protein localization or activity. Here we describe a previously unknown capability of a mutant of the photochromic FP Dronpa – light-dependent dissociation and association – and use it to control protein activities with light. Fusion of mutant Dronpa domains to both termini of an enzyme domain creates a fluorescent light-inducible protein that is inactive in the dark but can b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
279
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(282 citation statements)
references
References 32 publications
3
279
0
Order By: Relevance
“…56,57 In order to create a comprehensive data set with varying degrees of photobleaching or photoswitching to an off state, as a test whether macromolecular sedimentation properties could be modeled in all cases, the laser power of the 488 nm excitation beam was varied in consecutive experiments, using settings of 50.2 mW, 8.4 mW, and 2.1 mW. Lower laser power was partially compensated for by using higher photomultiplier voltages and gain settings to keep the signal/noise ratio high.…”
Section: Resultsmentioning
confidence: 99%
“…56,57 In order to create a comprehensive data set with varying degrees of photobleaching or photoswitching to an off state, as a test whether macromolecular sedimentation properties could be modeled in all cases, the laser power of the 488 nm excitation beam was varied in consecutive experiments, using settings of 50.2 mW, 8.4 mW, and 2.1 mW. Lower laser power was partially compensated for by using higher photomultiplier voltages and gain settings to keep the signal/noise ratio high.…”
Section: Resultsmentioning
confidence: 99%
“…Tools such as atomic force microscopy have been employed to measure changes in membrane tension [77,78] and could potentially be used to interactively manipulate tension as well. Optogenetic [7985] and chemical [86,87] tools may be used to rapidly modulate protein location/activity in living cells. Such approaches should provide further insight into the complex dance between signaling, forces, and the cytoskeleton that underlie the self-organization of protrusions and polarity.…”
Section: Future Directionsmentioning
confidence: 99%
“…In 2012, Lin and co-workers [62 ] reported that the green fluorescent Dronpa FP variant underwent an illumination-dependent change in oligomerization state. Upon illumination with cyan light (500 nm), the tetrameric Dronpa 145N variant dissociates to form a non-fluorescent monomeric protein.…”
Section: Fps As Optogenetic Actuatorsmentioning
confidence: 98%